Contemporary Uses of the Golden Rule of Reciprocity in Abrahamic Interfaith Discourses. (March 2018) - Untea, Ionut
The second half of the twentieth and the beginning of the twenty-first centuries have witnessed a revival of the Golden Rule arguments in relation to the idea of religious toleration. Apologizing or acknowledging apologies for past mistakes, the Abrahamic religions have produced a series of texts inviting further ethical and theological discussions with the purpose of facilitating reconciliation and working to maintain a sustainable world peace. Inspired by three groundbreaking texts, Nostra Aetate (1965), Dabru Emet (2000), and A Common Word (2007), representatives of all three monotheisms have produced a number of important commentaries, responses, and critiques with the purpose of clarifying some key points that both unite and separate the interpretations, given the familiar look of common doctrinal and moral teachings.